1995
DOI: 10.1007/bf00197342
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial citrate synthase from potato: predominant expression in mature leaves and young flower buds

Abstract: A cDNA clone encoding mitochondrial citrate synthase (EC 4.1.3.7), the first enzyme of the tricarboxylic-acid cycle, was isolated from potato (Solanum tuberosum L.) and expression of the enzyme analyzed. The deduced amino-acid sequence of the potato mitochondrial citrate synthase showed high similarity to known citrate synthases from fungi, mammals and Arabidopsis thaliana. The expression pattern of this clone was determined by Northern blot analysis. Expression was detected in all tissues analyzed. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Citrate synthase catalyses the condensation reaction occurring between the four-carbon oxaloacetate molecule and the two-carbon acetyl-CoA molecule and is often regarded as the first committed step of the tricarboxylic acid cycle (TCA; Landschü tze et al, 1995aLandschü tze et al, , 1995bFernie et al, 2004). Despite the strategic positional importance of this enzyme, studies that have investigated its metabolic importance in plants remain at a premium (Scheible et al, 2000;Bläsing et al, 2005;Pracharoenwattana et al, 2005;Urbanczyk-Wochniak et al, 2006).…”
mentioning
confidence: 99%
“…Citrate synthase catalyses the condensation reaction occurring between the four-carbon oxaloacetate molecule and the two-carbon acetyl-CoA molecule and is often regarded as the first committed step of the tricarboxylic acid cycle (TCA; Landschü tze et al, 1995aLandschü tze et al, , 1995bFernie et al, 2004). Despite the strategic positional importance of this enzyme, studies that have investigated its metabolic importance in plants remain at a premium (Scheible et al, 2000;Bläsing et al, 2005;Pracharoenwattana et al, 2005;Urbanczyk-Wochniak et al, 2006).…”
mentioning
confidence: 99%
“…Furthermore, in contrast to many other pathways of primary metabolism, the TCA cycle has been subjected to relatively few molecular physiological studies. To date, the functions of pyruvate dehydrogenase, citrate synthase, aconitase, isocitrate dehydrogenase, succinyl-CoA ligase, fumarase, and malate dehydrogenase have been studied via this approach (Landschü tze et al, 1995;Carrari et al, 2003;Yui et al, 2003;Nunes-Nesi et al, 2005, 2007aLemaitre et al, 2007; Studart-Guimarães et al, 2007); however, several of these studies were relatively cursory. Despite this fact, they generally corroborate one another, with at least two studies providing clear evidence for an important role of the TCA cycle in flower development (Landschü tze et al, 1995;Yui et al, 2003) or in the coordination of photosynthetic and respiratory metabolisms of the illuminated leaf Nunes-Nesi et al, 2005, 2007a.…”
mentioning
confidence: 99%
“…To date, the functions of pyruvate dehydrogenase, citrate synthase, aconitase, isocitrate dehydrogenase, succinyl-CoA ligase, fumarase, and malate dehydrogenase have been studied via this approach (Landschü tze et al, 1995;Carrari et al, 2003;Yui et al, 2003;Nunes-Nesi et al, 2005, 2007aLemaitre et al, 2007; Studart-Guimarães et al, 2007); however, several of these studies were relatively cursory. Despite this fact, they generally corroborate one another, with at least two studies providing clear evidence for an important role of the TCA cycle in flower development (Landschü tze et al, 1995;Yui et al, 2003) or in the coordination of photosynthetic and respiratory metabolisms of the illuminated leaf Nunes-Nesi et al, 2005, 2007a.In our own studies on tomato (Solanum lycopersicum), we have observed that modulation of fumarase and mitochondrial malate dehydrogenase activities leads to contrasting shoot phenotypes, with the former displaying stunted growth while the later exhibited an enhanced photosynthetic performance (Nunes-Nesi et al, 2005, 2007a. We were able to demonstrate that the stunted-growth phenotype observed in aerial parts of the fumarase plants was a consequence of altered stomatal function (Nunes-Nesi et al, 2007a), whereas the increased photosynthetic performance of the mi- * Corresponding author; e-mail fernie@mpimp-golm.mpg.de.…”
mentioning
confidence: 99%
“…Reproductive organs have high mitochondrial biogenesis activity 17,24,43,61,71 . Accordingly, if mitochondrial abnormalities can be ameliorated, rice fertility will improve in cold weather years.…”
Section: Perspective Of a Plant Organelle Biological Study Concerninmentioning
confidence: 99%